Assessment of the effects of artificial fungi inoculations on agarwood formation and sap flow rate of Aquilaria malaccensis Lam. using sonic tomography (SoT) and sap flow meter (SFM) - Jalil, Abd-Majid; Abdul-Hamid, Hazandy; Lias, Sahrim; Uyup, Mohd Khairun Anwar; Md. Tahir, Paridah; Mohd Razali, Sheriza; Mohd-Noor, Ahmad-Azaruddin; Ahmad Syazwan, Samsuddin; Shamsul-Anuar, Alliesya-Shamelia; Mohamad Kasim, Mohamad Roslan; Mohamed, Johar; Abiri, Rambod (MDPI, 2022)
Agarwood is a valuable aromatic resinous wood that is biosynthesised when a fungal attack injures the healthy wood tissue of the Aquilaria tree. The magnitude of infection related to sap flow (SF) is one of the most critical functional traits to evaluate the tree’s response to various adverse conditions. Therefore, the objective of this study was to investigate the reliability of sonic tomography (SoT) and sap flow meter (SFM) in studying the influence of inoculation fungi Pichia kudriavzevii Boidin, Pignal and Besson, and Paecilomyces niveus Stolk and Samson, on deteriorated wood (Dt) and SF rate in Aquilaria malaccensis Lam. A. malaccensis trees with small, medium, and large diameters were inoculated with each fungus separately at the bottom, middle, and top positions of the tree and the area of sapwood was measured after 6, 12, and 24 months to stimulate the agarwood formation. Furthermore, the SF rate was assessed using SFM in the position of the selected trees. There was a significant difference (p ≤ 0.05) in Dt% and SF rate between inoculated and uninoculated trees. The Dt percentage in trees inoculated with P. kudriavzevii, P. niveus, and control trees was 25.6%, 25.7%, and 15.0%, respectively. The SF rate was lower in P. kudriavzevii, with 207.7 cm3/h, than in the control trees, with 312.9 cm3/h in the small-diameter class. In summary, the results of this study emphasise the importance of inoculation duration (24 months) and the effects of water conductivity, especially tree diameter class (small), on the biosynthetic response of resinous substance.